Anatomy of a Dead Heat: Visual Evidence at the 2012 US Olympic Trials. - Finn, Jonathan (International Journal of the History of Sport, 2014)
The adoption and use of visual technologies as decision aids in professional sport is increasing at a rapid rate, yet the study of such practice is virtually non-existent. Beyond the specific play or call in question, images used as decision aids in sport have immediate and far-reaching material and cultural impacts including athlete sponsorship packages, the professional reputation and expertise of athletes and officials, and lucrative contracts for imaging and technology companies. This paper borrows Lorraine Daston and Peter Galison's work on objectivity to examine one such case: the dead heat between Jeneba Tarmoh and Allyson Felix at the 2012 US Olympic Trials. The Tarmoh/Felix dead heat involved a complex assemblage of human and machine vision, and contains within it many of the issues involved in the use of sports decision aids. The paper argues that analysis of images used as decision aids in sport have much to offer academic and non-academic audiences interested in sport and visual culture.